Sakato Plate Dance Choreography at Nagari Abai - Almadina Putri; Herlinda Mansyur (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to describe and analyze the Choreography of Sakato Plate Dance in Nagari Abai. The object of research studied was Sakato Plate Dance in Abai Sakato Art Studio, Nagari Abai. Stationery is used to record information or data obtained from sources and information related to Sakato Plate Dance. Photo Camera to take pictures of the form of motion and everything related to Sakato Plate Dance. Audio Recorder, this tool is used to record information about dance history, background, dance music and other information from informants and sources about Piring Sakato Dance. Primary data, namely data obtained from the main source, namely the choreographer of Sakato Plate Dance. Secondary data, which is supporting research data obtained through data that has been collected or the results of relevant research, then the data is also obtained from documentation owned by the Sakato Plate Dance choreographer in the form of photos, video recordings and others. The analysis steps taken are, the data is selected as needed and related to the problem posed, namely about the Sakato Plate Dance Choreography then arranged systematically and descriptively. The energy aspect used in this Sakato Plate Dance is that there is slow, medium, and strong energy this aspect aims to beautify the Sakato Plate Dance. As for the interaction that occurs in the Sakato Plate Dance, the property used in this Sakato Plate Dance is a plate with a plate size of 5. The clothes used in the Sakato Plate Dance are costumes that have been created so that dancers are easy to make movements and are not disturbed when holding plates.